Optimalisasi Program BRASTIM dalam Mendukung Pembangunan Ekonomi Berbasis Kerakyatan - Hanifah Permana (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study is motivated by the importance of ensuring food security for poor households and orphans as part of people-centered economic development. The research aims to describe the implementation of the Rice Assistance Program in Aur Kuning Subdistrict, identify obstacles in data collection, distribution, and supervision, and formulate strategies to optimize the program. The study employs a descriptive qualitative approach based on library research, using content analysis to examine the program’s role in maintaining household food security and improving community economic welfare. The findings show that the program significantly contributes to sustaining food availability, reducing household expenditure burdens, and enhancing purchasing power. However, several issues remain, including mistargeted beneficiaries, distribution delays, and weak monitoring mechanisms. The discussion highlights the need for improved governance, strengthened data management, and increased transparency to ensure that the program operates more effectively and sustainably in supporting community-based economic development.